2013
DOI: 10.1155/2013/503270
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Risk Factors Related to Vitamin D and Adiponectin in Obese Children and Adolescents

Abstract: Obesity-related diseases are becoming the most important causes of mortality worldwide. Several studies have suggested an association between low levels of vitamin D and obesity. In addition, plasma adiponectin levels have been found to be lower in obese subjects. We evaluated the association of metabolic risk factors with both adiponectin and vitamin D levels and that between adiponectin and vitamin D levels. The study consisted of 114 obese and healthy subjects. 25-Hydroxy vitamin D [25(OH)D] levels were pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 33 publications
3
32
2
1
Order By: Relevance
“…This result has been found to be similar to Kardas and his colleagues, [11] in Turkey. Abu Shady et al, [24], also found inverse association of serum 25(OH) D with BMI among 215 Egyptian school children, but with insignificant relation with age and sex.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This result has been found to be similar to Kardas and his colleagues, [11] in Turkey. Abu Shady et al, [24], also found inverse association of serum 25(OH) D with BMI among 215 Egyptian school children, but with insignificant relation with age and sex.…”
Section: Discussionsupporting
confidence: 90%
“…This result agreed with Walker et al, [6] in Italy. In contrast, some recent studies have suggested that 25(OH)D may play a role in the regulation of adiponectin [11,15]. Adiponectin was identified and confirmed to be significantly decreased in 25(OH)D deficient obese pediatric [16].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations